Lung herniation after minimally invasive cardiothoracic surgery - Weymann, Alexander; Szabó, Gábor (The New England journal of medicine, 2011)
One year after undergoing minimally invasive direct coronary-artery bypass surgery, a 67-year-old man was admitted to hospital with a well-demarcated deformity overlying the third intercostal space of the left anterior hemithorax. On examination, the lesion had a positive cough impulse and spontaneous reduction with inhalation. Breath sounds could be clearly heard within the mass. Computed tomographic images of the chest confirmed that a large portion of the lung had herniated through an intercostal defect in the chest wall (Panel A, arrow, axial view; Panel B, arrow, sagittal view). Lung herniation is a rare complication of minimally invasive cardiothoracic surgery. In . . .